2022
DOI: 10.1108/ijhrh-04-2022-0028
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing making a choice and accessing a hearing aid among elders with hearing disability: mixed methods

Abstract: Purpose Hearing aid (HA) using is an option for enhancing the sound transmission. It effectively improves hearing ability during communication. In Thailand, two-third of hearing impaired persons were elders, while the utilization of an HA was low. This study aims to explore how the decision was made on the use of HA among the hearing impaired elderly. Design/methodology/approach Mixed-methods sequential explanatory design was used by starting with a retrospective study to identify the prevalence of HA use an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Problems related to the initial fitting of hearing aids, including ear discomfort and dizziness, have discouraged hearing aid users from continuing to wear the device. Many of these could be resolved by accessing audiological counselling, care and rehabilitation ( 26 ). First time visits should also consist of training for practical usage, for instance insertion, removal, functions, and maintenance of hearing aids.…”
Section: Discussionmentioning
confidence: 99%
“…Problems related to the initial fitting of hearing aids, including ear discomfort and dizziness, have discouraged hearing aid users from continuing to wear the device. Many of these could be resolved by accessing audiological counselling, care and rehabilitation ( 26 ). First time visits should also consist of training for practical usage, for instance insertion, removal, functions, and maintenance of hearing aids.…”
Section: Discussionmentioning
confidence: 99%
“…In low-and middle-income countries, over 85% of individuals who need hearing aids lack access to the same [7]. In southern Thailand, it was revealed that nearly 50% of individuals with hearing disabilities lived more than 100 km away from a main audiology and hearing aid center, Songklanagarind Hospital, which required at least 2 h of driving [8].…”
Section: Introductionmentioning
confidence: 99%